Aportes de la Educación Musical en el Ámbito Emocional. Estado de la Cuestión en Colombia. (2021)
Music is a universal means of expression that affects different emotional, social, and cultural factors in people. Consequently, musical training is a scenario of significant contributions to the integrality of the subject. The intra- and interpersonal sphere is one of the dimensions that is most positively impacted by music. This article discusses the results of a review of Colombian publications that highlight the psychological approach to music education in the country and the impact of musical education on the emotions of girls, boys, and adolescents. The results show a growing body of research which denotes the incidence of musical training in the development of interpersonal skills and in strengthening the intrapersonal environment of students.